2020 International Joint Conference on Neural Networks (IJCNN) 2020
DOI: 10.1109/ijcnn48605.2020.9207427
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating Reinforcement Learning for Reaching Using Continuous Curriculum Learning

Abstract: Reinforcement learning has shown great promise in the training of robot behavior due to the sequential decision making characteristics. However, the required enormous amount of interactive and informative training data provides the major stumbling block for progress. In this study, we focus on accelerating reinforcement learning (RL) training and improving the performance of multi-goal reaching tasks. Specifically, we propose a precision-based continuous curriculum learning (PCCL) method in which the requireme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…Learning varying obstacle distribution and end-effector positions simultaneously is very difficult. Therefore, we design a two-stage learning strategy motivated by curriculum learning [ 27 ]. In Stage I, the manipulator starts from a fixed configuration and learns to avoid obstacles in null space.…”
Section: Methodsmentioning
confidence: 99%
“…Learning varying obstacle distribution and end-effector positions simultaneously is very difficult. Therefore, we design a two-stage learning strategy motivated by curriculum learning [ 27 ]. In Stage I, the manipulator starts from a fixed configuration and learns to avoid obstacles in null space.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, they presented a recursive algorithm that receives environment information as point-clouds, as well as a robot's initial and desired goal configurations as input arguments and generates connectable path as an output. Some other researches also demonstrated segmenting motion tasks could reduce the complexity that the lower modules have to deal with [120]. Whether it is by distinguishing between individual tasks based on relations of touch [5] or embedding scores or attractors directly into a robotic joint feature space [74].…”
Section: Avoiding Collisions With the Environmentmentioning
confidence: 99%
“…It has also been shown that the development of a simple curriculum based on the accuracy requirements of a given task, on basis of a measure of a degree of competence like [20], leads to faster and more efficient training [21]. An extension to the work with Universal Value Function Approximators (UVFA) [22] is studied in [23]. While the current state of research mostly focusses on simulated objectives, notable efforts are being put into introducing simulation-trained intelligent and highly adaptive agents to the real-world [24][25][26].…”
Section: Curriculum Learningmentioning
confidence: 99%